Ионно-иммерсионная имплантация алюминия в титан ВТ1-0; Известия РАН. Серия физическая; Т. 80, № 2 - Никитенков Н. Н. Николай Николаевич; Сутыгина А. Н. Алина Николаевна; Шулепов И. А. Иван Анисимович; Кашкаров Е. Б. Егор Борисович (2015, 2015)
Заглавие с экрана